Analisis Kualitas Briket Serbuk Gergaji Kayu Dengan Penambahan Tempurung Kelapa Sebagai Bahan Bakar Alternatif - Saleh, Asri; Novianty, Iin; Murni, Suci; Nurrahma, Andi (Al-Kimia, 2017)
Increasing fuel and liquid gas prices make this energy source is no longer cheap. Therefore, it is necessary to create an alternative energy resource that can be used to replace the role of fuel and gas. Waste sawdust and coconut shell has a huge potential that can be used as raw material charcoal briquettes. The purpose of this research is to improve the quality of sawdust briquettes with the addition of coconut shell charcoal. To improve the quality of charcoal briquettes, the addition of coconut shell charcoal with a variation of 20%, 30%, 40%, 50% and 60% of the weight of sawdust briquette charcoal. Authoring process is done by burning coconut shells directly and roasting methods to sawdust. Adhesives are used as much as 50%. The calorific value generated in sawdust briquettes with materials: coconut shell at a concentration of 100% is 5622.7769 cal/gram, a concentration of 80: 20% is 6504.67785 cal/gram, the concentration of 70: 30% is 6624.09305 cal/gram, the concentration of 60: 40% is 7017.5178 cal/gram, a concentration of 50: 50% is 7288.7523 cal/gram and 40: 60% is 7386.4805 cal/gram. Overall, the quality of sawdust briquettes with palm shell charcoal is quite good, so it can be used as an alternative fuel